Economic Convergence in the EU: A Complexity Approach - Gül Ertan Özgüzer; Ayla Oæguøs (Izmir University of Economics, Department of Economics, 2015)
This paper tests, in the context of the EU countries, the evidence presented by Hidalgo and Hausmann (2009) that economic complexity indicator is a good predictor of economic growth. Our results suggest that a group of countries in the EU with an economic complexity exceeding a certain threshold tends to converge to the levels of income corresponding to their measured complexity. On the other hand, current account deficits in interaction with economic complexity have important effects on growth for a second group of countries with lower levels of complexity. We also find that income convergence is faster within the first group. Therefore, we argue that convergence is much faster for countries whose economic complexity exceeds a certain threshold.
Keywords: O11; O52; F43; 330; economic complexity; growth; income convergence; European Union; heterogeneity